2017
DOI: 10.1016/j.bbi.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-reactive protein in adolescence and risk of schizophrenia in adulthood: A prospective birth cohort study

Abstract: HighlightsThis is one of the first longitudinal studies of serum CRP & subsequent schizophrenia.Elevated serum CRP in adolescence is associated with risk of adult schizophrenia.The CRP-schizophrenia association is consistent with a dose-response relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 53 publications
(63 reference statements)
7
90
1
1
Order By: Relevance
“…The results showed a direct, and a linear relation between blood CRP levels in adolescents and later risk for SCZ. Others have shown that higher levels of CRP are associated with earlier age of disease onset (Metcalf et al, ). Still other studies have shown the effects of immune modulation on amyloidosis, a hallmark of Alzheimer's disease (Philippens et al, ).…”
Section: Mechanisms Through Which Infection and Inflammation May Indumentioning
confidence: 99%
“…The results showed a direct, and a linear relation between blood CRP levels in adolescents and later risk for SCZ. Others have shown that higher levels of CRP are associated with earlier age of disease onset (Metcalf et al, ). Still other studies have shown the effects of immune modulation on amyloidosis, a hallmark of Alzheimer's disease (Philippens et al, ).…”
Section: Mechanisms Through Which Infection and Inflammation May Indumentioning
confidence: 99%
“…Levels of circulating inflammatory marker C-reactive protein (CRP) were associated with schizophrenia by the age of 27 years [78]. Finally, parental somatic illness in childhood may also increase psychosis risk in the offspring.…”
Section: Somatic Health and Risk For Psychosismentioning
confidence: 99%
“…Individuals with persistent or acutely elevated inflammatory biomarkers, such as C‐reactive protein (CRP), are at increased risk of schizophrenia (Metcalf et al, ; Wium‐Andersen, Orsted, & Nordestgaard, ) and depression (Wium‐Andersen, Orsted, Nielsen, & Nordestgaard, ). Elevated levels of inflammation at baseline have further been suggested to contribute to treatment resistance in depression (Strawbridge et al, ; Uher et al, ); however, it remains unclear whether inflammatory markers are associated with treatment resistance in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%